(untitled) (University Heart Journal, 2026)
Background: Chronic kidney disease (CKD) is increasingly recognized as an important and independent risk factor for cardiovascular disease. Patients with CKD frequently present with acute coronary syndromes (ACS) and demonstrate worse short- and long-term outcomes compared with those with preserved renal function. Non–ST elevation acute coronary syndrome (NSTE-ACS) represents a heterogeneous clinical spectrum, and renal dysfunction significantly influences disease severity, treatment decisions, and prognosis. Objectives: To evaluate and compare the coronary angiographic characteristics of patients presenting with NSTE-ACS with and without chronic kidney disease. Methods: This prospective observational study included 60 consecutive patients diagnosed with NSTE-ACS and admitted to the Department of Cardiology, Bangladesh Medical University, between December 2024 and December 2025. Patients were divided into two groups based on estimated glomerular filtration rate (eGFR): CKD group (eGFR <60 mL/min/1.73 m²; n=30) and non-CKD group (eGFR ≥60 mL/min/1.73 m²; n=30). Baseline demographic characteristics, cardiovascular risk factors, laboratory parameters, echocardiographic findings, and coronary angiographic features were analyzed and compared. Results: Patients with CKD were significantly older and had a higher prevalence of hypertension and diabetes mellitus. Coronary angiography revealed a higher frequency of multi vessel coronary artery disease, complex lesions, and left main coronary artery involvement among CKD patients compared with non-CKD patients. Conclusion: Chronic kidney disease is associated with more extensive and severe coronary artery disease in patients presenting with NSTE-ACS. Early recognition of renal dysfunction may aid in improved risk stratification and management strategies in this high-risk population. University Heart Journal 2026; 22(1): 3-6